PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERAWAT DALAM MELAKUKAN TERAPI MINDFULLNESS - ., Ardinata; Susanto, Agus (JURNAL ILMU KEPERAWATAN INDONESIA (JIKI), 2019)
Background : Leadership is the process of influencing others to collaborate productively and in conditions that are pleasant and focused on humans. Factors of the success of an organization lie in the leadership style used in the organization. Purpose: The purpose of this study was to examine the impact of the leadership style of nurse managers in Saudi and nurse satisfaction and their intention to continue working. Method : This systematic review is obtained through a comprehensive search method for all Comprehensive literature searches. The literature material on this systematic review was carried out in the period of time between 2005 and 2017. Results and Discussion: leadership is very influential on service quality, environment and workload, transformational leadership is able to make the quality of health services increase as the work environment improves and the workload decreases because subordinates feel it is an important part of their work. Conclusion: transformational leadership has a positive effect to reduce the workload of nurses in hospitals.